Worldwide variations in the knowledge and use of fluoroscopy during percutaneous nephrolithotomy—should we do better? A survey by the European Association of Urology Section for Uro-Technology and the International Alliance of Urolithiasis - Otaš Durutovic; Guohua Zeng; Bhaskar Somani; Simon Choong; Giorgio Mazzon; Di Gu; Zeeshan Hameed; TP Rajeev; Bogomir Milojevic; Davide Brusa; Tiago Ribeiro Oliveira; Sergio Pereira; et al. (Asian Journal of Urology)
Objective: This study aimed to investigate the level of knowledge among urologists of usage of fluoroscopy during percutaneous nephrolithotomy. Methods: We conducted an anonymous internet-based survey addressed to the EAU Section of Uro-Technology and the International Alliance of Urolithiasis members with particular interest in the stone treatment at all levels of expertise. The final version of the questionnaire included 31 questions, evaluated the level of knowledge on X-ray utilization and exposure, and identified correlations between geographic areas, levels of seniority, surgical volumes, and awareness on radiation protection. Results: In total, 586 respondents were included. Knowledge of fluoroscopy settings appeared low, particularly among trainees (up to 87.5% were uninformed, p=0.008). Precautions to reduce exposure appeared poorly followed as up to 25.4% of respondents used regularly continuous fluoroscopy, and up to 20.5% used regularly high-frequency setting and this trend was more obvious among senior specialists (6.2% of trainees used high-frequency settings vs. 21.3% of consultants, p<0.05). Additionally, only 24.9% of respondents would provide X-ray protection to patients too. Conclusion: Although high and routinary utilization of X-rays, the level of awareness and adhesion to “as low as reasonably achievable” principles among endourologists seems suboptimal in 65.0% of all respondents. Highest volume surgeons, inevitably at higher risk, do not seem to adopt more precautions. More efforts should be addressed to improve these results, reducing the risk related to excessive radiation exposure for both surgical staff and patients in order to minimize health related issues.